Effect of dentin conditioning time on nanoleakage - Duarte, S.; Perdigao, J.; Lopes, M. M. (Operative Dentistry Inc, 2006)
Objectives: To study the nanoleakage pattern in the dentin hybrid layer by using different dentin adhesives. The null hypotheses tested in this study were: 1) dentin conditioning time does not affect nanoleakage within the hybrid layer; 2) the type of dentin adhesive used does not affect nanoleakage. Methods: Standardized Class V cavities were prepared in 30 intact human molars on the buccal and lingual surfaces. The specimens were randomly assigned to 2 total-etch dentin adhesives (OptiBond SOLO Plus [OPS, Kerr] and One-Step [ONS, BISCO Inc]) and 2 self-etch dentin adhesives (Clearfil SE Bond [CSE, Kuraray] and Adper Prompt L-Pop [APL, 3M ESPE]). The specimens were etched or conditioned for 15 seconds, 30 seconds or 60 seconds. Upon restoration of the Class V cavities with the proprietary resin composite, the specimens were isolated with nail polish except for a 2.0-mm rim around the restoration, and they were immersed in 50 wt% ammoniacal silver nitrate solution (pH=9.5) for 24 hours followed by 8 hours of immersion in photo-developing solution to reduce the silver ions to metallic silver. The specimens were fixed, dehydrated and processed for FESEM and TEM. Silver penetration was measured along the cervical wall, and data were analyzed with Kruskal-Wallis non-parametric tests at a significance level of 95%. Results: There were no statistically significant differences among the experimental groups for the factor conditioning time (p>0.926). There were significant differences for the variable dentin adhesive (p<0.0001). The least amount of nanoleakage within the hybrid layer occurred with CSE, while ONS resulted in the greatest penetration of silver ions. The adhesives OPS and APL ranked in the intermediary subset. Under TEM, all adhesives resulted in some degree of nanoleakage within the hybrid layer. Both spotted/reticular and water-tree nanoleakage patterns were observed. Significance: Longer conditioning times did not increase nanoleakage within the hybrid layer. Nanoleakage varied with the type of adhesive used.